The embryonic stem cell factor UTF1 serves as a reliable diagnostic marker for germinomas - Pantazis, Georgios; Harter, Patrick N.; Capper, David; Kohlhof, Patricia; Mittelbronn, Michel; Schittenhelm, Jens (Pathology, 2016)
The transcription factor OCT4 is an established diagnostic marker for central nervous system (CNS) germinoma. However, no data are available to date concerning the expression of its downstream target undifferentiated embryonic cell transcription factor 1 (UTF1) in CNS germ cell tumours. We examined 21 CNS germinomas and two mixed CNS germ cell tumours for UTF1 and the post-transcriptional regulator LIN28 immunohistochemical expression. We compared the profile to established diagnostic germinoma markers and to the expression in six testicular and four metastatic germ cell tumours as well as 150 CNS tumours of various backgrounds.
Available online 23 February 2016
Gesehen am 09.09.2020